Magnetic cobalt particle-assisted solid phase extraction of tellurium prior to its determination by slotted quartz tube-flame atomic absorption spectrophotometry - Ozdogan, Nizamettin; Kapukiran, Fatih; Er, Elif Ozturk; Bakirdere, Sezgin (SPRINGER, 2019)
The emergence of magnetic materials has opened up doors to numerous applications including their use as sorbents for preconcentration of trace elements. Magnetic materials exhibit many unique advantages in sample preparation such as easy separation from the sample, high preconcentration factor, and short operation period. In the present study, magnetic cobalt material was synthesized, characterized, and used as an effective sorbent in a solid phase extraction process. Experimental variables of the extraction process including pH and volume of buffer solution, eluent concentration and volume, mixing type and period, and sorbent amount were optimized to achieve maximum extraction efficiency. Instrumental variables of flame atomic absorption spectrophotometry and the type of slotted quartz tube were also investigated. Under the optimum conditions, the combined method provided a wide linear range between 50 and 200ng/mL with detection and quantification limits of 15.4ng/mL and 51.3ng/mL, respectively. Relative standard deviations of the proposed method were less than 5.0% and a high enrichment factor of 86.7 was obtained. The proposed method was successfully applied to soil samples for the determination of trace tellurium.
Keywords: Tellurium; Slotted quartz tube; Flame atomic absorption spectrophotometry; Magnetic solid phase extraction; INORGANIC TELLURIUM; ICP-MS; PRECONCENTRATION; SELENIUM; WATER; ANTIMONY; SAMPLES; BISMUTH; MICROEXTRACTION; COPRECIPITATION; Environmental Sciences & Ecology